FinTech in Sub-Saharan African Countries : A Game Changer? - Sy, Amadou (Departmental Papers; Departmental Paper ;, 2019)
FinTech is a major force shaping the structure of the financial industry in sub-Saharan Africa. New technologies are being developed and implemented in sub-Saharan Africa with the potential to change the competitive landscape in the financial industry. While it raises concerns on the emergence of vulnerabilities, FinTech challenges traditional structures and creates efficiency gains by opening up the financial services value chain. Today, FinTech is emerging as a technological enabler in the region, improving financial inclusion and serving as a catalyst for the emergence of innovations in other sectors, such as agriculture and infrastructure.